First records of the blurred lantern shark Etmopterus bigelowi from the Cayman Islands, Western Atlantic - Gallagher, Austin J.; Shipley, Oliver N.; De Silva, Christine; Kohler, Johanna K.; Fernandes, Teresa F.; Austin, Timothy; Ormond, Rupert F.; Gore, Mauvis A. (Frontiers in Marine Science, 2023)
The genus Etmopterus is the most speciose group of small bodied deep-sea sharks found throughout the tropical and subtropical Western Atlantic. Despite exhibiting a global distribution at the genus-level, the blurred lantern shark (Etempoterus bigelowi) is known only from a few records in the Western and Southern Atlantic Ocean. Through in-situ video observations using deep-sea landers, we provide two new locality records of the blurred lantern shark from the deep waters off the Cayman Islands, Caribbean Sea. Three unique individuals were recorded across two separate deployments between 653m – 668m. These observations provide the first records of this species in the Caribbean Sea, adding to the minimal knowledge of the species’ distribution throughout the Western Atlantic Ocean.